2012
DOI: 10.1021/np3000365
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Carbazole Alkaloids from Clausena wallichii Roots

Abstract: Four new carbazole alkaloids, clausenawallines C-F (1-4), along with 18 known compounds (5-22) were isolated from the roots of Clausena wallichii. Compounds 3, 9, and 22 exhibited significant antibacterial activity against methicillin-resistant Staphylococcus aureus SK1 (MRSA SK1) and Staph. aureus TISTR 1466 with MIC values in the range 4-16 μg/mL, whereas compound 4 showed the highest cytotoxicity against oral cavity cancer (KB) and small-cell lung cancer (NCI-H187) with IC(50) values of 10.2 and 4.5 μM, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…[22] Theb iscarbazole alkaloids exhibit potent biological activity and are challenging targets for total synthesis. [18] We employed an ovel copper chloride mediated CÀCc oupling in the presence of DBU to synthesize bis(2-hydroxy-3-methylcarbazole)( 9)i n5 1% yield. Recently,t he Knçlker group reported the first total synthesis of girinimbilol (mukoenine A, 11)b yo pening of the pyran ring of girinimbine.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[22] Theb iscarbazole alkaloids exhibit potent biological activity and are challenging targets for total synthesis. [18] We employed an ovel copper chloride mediated CÀCc oupling in the presence of DBU to synthesize bis(2-hydroxy-3-methylcarbazole)( 9)i n5 1% yield. Recently,t he Knçlker group reported the first total synthesis of girinimbilol (mukoenine A, 11)b yo pening of the pyran ring of girinimbine.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thec arbazole alkaloidsmukonal [15] and bis(2-hydroxy-3-methylcarbazole) [18] are isolated from the stem bark of Murraya koenigii.Girinimbilol [16] and heptaphylline [16] are isolated from both the stem bark of Murraya koenigii and root bark of Clausena heptaphylla.…”
mentioning
confidence: 99%
“…Compounds clausenawallines E (9), 2,7-dihydroxy-3-form-yl-1-(3′-methyl-2′-butenyl) carbazole (10) and clausenawalline B (11) were isolated from the roots of C. wallichii, which exhibited significant antibacterial activity against MRSA SK1 with MIC values in the range of 4-16 μg/mL. [11] In addition, three alka- (17) showed significant anti-MRSA effects (MIC = 8, 16, 16 μg/mL, respectively). [13] The leaves extract of Platanus occidentalis also exhibited potent anti-MRSA activity.…”
Section: Alkaloidsmentioning
confidence: 99%
“…F by Ito et al,3 from Clausena vestita D. D. Tao by Zhao et al,4 and from Clausena wallichii by Laphookhieo et al5 In 1990, Lange et al reported the first isolation of the corresponding methyl ether, 7‐methoxy‐ O ‐methylmukonal ( 2 ), from the roots of Murraya siamensis , which was collected in Thailand 6. Subsequently, compound 2 was also isolated from Clausena excavata by Wu et al,7 from Clausena vestita D. D. Tao by Zhao et al,4 and from the roots of Clausena wallichii by Laphookhieo and co‐workers 5. A variety of biological activities has been reported for 7‐methoxymukonal ( 1 ) and 7‐methoxy‐ O ‐methylmukonal ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kongkathip and co‐workers observed that 7‐methoxymukonal ( 1 ) displays weak antimycobacterial activity against the H 37 Ra strain and weak antifungal activity against Candida albicans 9. Furthermore, cytotoxicity against the MCF‐7 cell line (breast cancer) and the KB cell line (oral human epidermal carcinoma),5,10 antimalarial activity,10a weak antioxidant activity, and an inhibition of lipid peroxidation have been described for 1 11. In 2005, Kongkathip and co‐workers reported anti‐HIV activity for 7‐methoxy‐ O ‐methylmukonal ( 2 ) 12…”
Section: Introductionmentioning
confidence: 99%